DZIKIR RATIB AL-HADDAD AS AN EFFORT TO STRENGTHEN RELIGIOUS CHARACTER EDUCATION - Azizah, Alvi Nur; Rohmadi, Yusup (Nurul Jadid University, Paiton Probolinggo, East Java, 2022)
This research was conducted because people are increasingly losing their character and identity as an excellent Indonesian nation, and the low public awareness of religious activities. For this reason, this study aims to analyze and examine the remembrance of Ratib Al-Haddad to strengthen religious character education. The approach used in this research is a descriptive qualitative type of case study. Data collection uses observation and in-depth interviews and is supported by documentation. The research location is in Kaling Village, Tasikmadu District, Karanganyar Regency. Data analysis techniques used are data collection, data reduction, data presentation, and data inference. The results showed that efforts to strengthen religious character education in Kaling Village provided the community an understanding of religious character through remembrance of Ratib Al-Haddad activities led by Kyai. Strengthening character education through remembering Ratib Al-Haddad includes moral knowing, feeling, and doing. This research implies that all parties need support to achieve a common goal, namely creating a harmonious religious character.